Meibomian gland features in a Norwegian cohort of patients with primary Sjögren´s syndrome. - Xiangjun Chen; Øygunn Aass Utheim; Jiaxin Xiao; Muhammed Yasin Adil; Aleksandar Stojanovic; Behzod Tashbayev; Janicke Liaaen Jensen; Tor Paaske Utheim (PLoS ONE, 2017)
Purpose To assess the tear film and meibomian gland (MG) features in a Norwegian cohort of patients with primary Sjögren´s syndrome (pSS) and in age- and gender-matched control subjects. Methods Thirty-four female patients with pSS (age 52.9±11.9 years) and 32 female control subjects (age 49.0±11.5 years) were recruited. After completion of Ocular Surface Disease Index (OSDI) questionnaire and McMonnies Dry Eye Questionaire, participants underwent measurements of tear osmolarity, tear break-up time (TBUT), ocular surface and corneal staining, Schirmer I test, corneal sensitivity, MG expressibility evaluations, and lid margin morphology examination using slitlamp microscopy. Non-contact infrared meibography images were assessed by computer-assisted analysis. The MG loss, calculated as (tarsal area-MG area)/tarsal area, was evaluated in both upper (UL) and lower lids (LL). Results Compared to the control group, pSS patients demonstrated higher MG loss in both UL (33.8±13.2% vs. 24.4±8.5%, p< 0.01) and LL (52.5±15.7% vs. 43.0±9.6%, p<0.05), as well as higher lid abnormality score (0.8±0.8 vs. 0.2±0.6, p< 0.01). Furthermore, pSS patients showed higher OSDI and McMonnies questionnaire scores, elevated osmolarity, shorter TBUT, shorter blink interval, less wetting in Schirmer I test, more ocular surface staining and more corneal staining. MG loss in UL correlated negatively with TBUT (r = -0.386, p = 0.029) in the pSS group, whereas MG loss in LL correlated negatively with TBUT (r = -0.380, p = 0.035) in the control group. Conclusions Significantly elevated dry eye symptoms and signs were found in the pSS group compared with the control group, which might be attributed to both decreased aqueous tear production and increased tear evaporation.